THE POTENTIAL APPLICATION OF ENVIRONMENTAL TAXATION IN THE FISHERIES SECTOR: A QUALITATIVE REVIEW THROUGH THE LENS OF BLUE ACCOUNTING IN THE ARU ISLANDS REGENCY - Ester Melania Pasamba (Komunitas Manajemen Kompetitif, 2026)
This study aims to describe the potential application of environmental taxes in the fisheries sector in Aru Islands Regency through the perspective of Blue Accounting. A descriptive qualitative approach was applied with data collection techniques through in-depth interviews with 15 key informants, including local government officials, fisheries business actors, and traditional fishermen, supported by field observations and document studies. The findings reveal that conceptually there is significant potential for implementing environmental taxes, particularly in the form of taxes/levies on fishing vessel fuel and taxes on destructive fishing gear. However, implementation faces complex challenges in the form of fragmented understanding of Blue Accounting at the local government level, polarized perceptions between traditional fishermen who are concerned about the economic burden and business actors who want transparency in fund allocation, and limited institutional capacity. Through the lens of Blue Accounting, this study recommends a progressive policy model that integrates local wisdom such as Sasi Laut with modern fiscal instruments, implements a system of earmarking funds specifically for ecosystem conservation, and establishes accountability mechanisms that include ecological performance indicators. The study concludes that the implementation of environmental taxes in the Aru Islands requires a gradual and contextual approach, starting with pilot projects, with a paradigm shift from taxes as a burden to collective investment in preserving natural capital for long-term ecological and economic sustainability.